2011
DOI: 10.1007/s12595-011-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of Lycopene in Mammalian System: A Review

Abstract: Lycopene is an open chain 'hydrocarbon carotenoid' without provitamin A activity, which gives tomato, pink grape fruit, watermelon etc. their red colour. It is a powerful antioxidant that has been shown to neutralize free radicals, especially those derived from oxygen, thereby conferring protection against prostate cancer, breast cancer, atherosclerosis and associated coronary artery disease etc. It reduces (L.D.L) low-density lipoprotein oxidation and helps reduce cholesterol levels in the blood. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The iron-supplemented liver presented morphological changes associated with proliferation and autophagy but no apoptosis, damages prevented by lycopene pre-treatment. Dietary intakes of tomatoes and tomato products containing lycopene have been shown to be associated with decreased risk of chronic diseases such as cancer and cardiovascular diseases in several recent studies (Huang and Hu, 2011;Sharma and Goswami, 2011). In this study, we noted the increase in food ingestion observed in rats with lycopene supplementation.…”
Section: Ultrastructural Alterations and Autophagy In Liversupporting
confidence: 59%
See 1 more Smart Citation
“…The iron-supplemented liver presented morphological changes associated with proliferation and autophagy but no apoptosis, damages prevented by lycopene pre-treatment. Dietary intakes of tomatoes and tomato products containing lycopene have been shown to be associated with decreased risk of chronic diseases such as cancer and cardiovascular diseases in several recent studies (Huang and Hu, 2011;Sharma and Goswami, 2011). In this study, we noted the increase in food ingestion observed in rats with lycopene supplementation.…”
Section: Ultrastructural Alterations and Autophagy In Liversupporting
confidence: 59%
“…In these last decades, there was growing interest in the association of specifi c components of human nutrition and oxidative stress (Morihara et al, 2006;Dairam et al, 2008). Lycopene, a carotenoid compound, occurring naturally in tomato and other fruits like papaya, pink guava and watermelon has been shown to neutralize free radicals, especially those derived from oxygen, thereby conferring protection against cancer of the prostate, breast, lung, bladder, cervix and skin, atherosclerosis and associated coronary artery disease (Sharma and Goswami, 2011). Dietary intakes of cooked tomatoes and their by-products account for 90% of the lycopene in the average Southern and North American diet (Bose and Agrawal, 2007;Garciaalonso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This response can include stimulating DNA repair pathways, as well as antioxidative agents. In addition to a putative role in regulating membrane fluidity (discussed above), heightened synthesis of the carotenoid lycopene in P. halocryophilus under cold conditions would also be important in the oxidative response, as it is known to neutralize free oxygen radicals (Sharma and Goswami, 2011). As a carotenoid, it would also mitigate potential oxidative stress from UV radiation.…”
Section: Oxidative and Carbonyl Stressmentioning
confidence: 99%
“…Lycopene (Ly), the most common type of carotenoid in dietary intake, has been shown to confer protective effects against ageing, tissue damage, certain types of cancer, atherosclerosis and associated coronary artery disease (10). Possible mechanisms of Ly-mediated effects are via antioxidant activity, increases in gap-junctional intercellular communication, cell growth control, the activation of the mevalonic acid pathway, suppressing the expression of the oncogene ras and the modulation of immune responses (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%